Evolution of Quality Assurance for Clinical Immunohistochemistry in the Era of Precision Medicine: Part 4. Issue 4 (April 2017) - Cheung, Carol C.; D'Arrigo, Corrado; Dietel, Manfred; Francis, Glenn D.; Fulton, Regan; Gilks, C. Blake; Hall, Jacqueline A.; Hornick, Jason L.; Ibrahim, Merdol; Marchetti, Antonio; Miller, Keith; van Krieken, J. Han; et al.
Abstract : The numbers of diagnostic, prognostic, and predictive immunohistochemistry (IHC) tests are increasing; the implementation and validation of new IHC tests, revalidation of existing tests, as well as the on-going need for daily quality assurance monitoring present significant challenges to clinical laboratories. There is a need for proper quality tools, specifically tissue tools that will enable laboratories to successfully carry out these processes. This paper clarifies, through the lens of laboratory tissue tools, how validation, verification, and revalidation of IHC tests can be performed in order to develop and maintain high quality "fit-for-purpose" IHC testing in the era of precision medicine. This is the final part of the 4-part series "Evolution of Quality Assurance for Clinical Immunohistochemistry in the Era of Precision Medicine."